Type 2 diabetes, healthcare expenditures and its correlation with anthropometric factors and physical activity: 18-month follow-up in a Brazilian city - Araujo, Monique Yndawe Castanho [UNESP]; Turi, Bruna Camilo [UNESP]; Queiroz, Dayane Cristina [UNESP]; Dos Santos Ferro, Izabela [UNESP]; Bortolatto, Carolina Rodrigues [UNESP]; Codogno, Jamile Sanches [UNESP] (FapUNIFESP (SciELO), 2018)
Aims: To compare the profile of adults attended at primary care level of the Brazilian National Health System according to occurrence of T2DM during 18 months of follow-up. Method: Longitudinal study carried out with 316 adults. T2DM and PA were assessed by questionnaires. Measurements of weight, height and waist circumference (WC) were also performed. Healthcare expenditures were based on the demand of services registered in medical records. Analysis of variance (ANOVA) with Tukey's post hoc test was used, as well as their similar for non-parametric variables. Spearman's correlation coefficient analyzed the relationship between variables. All analyzes were performed using the statistical software BioEstat (release 5.0) and the significance level was set at p-value < 0.05. Results: Patients with T2DM at baseline showed higher values of WC, BMI, nursing appointments, customer services, medication, total cost and lower values of PA when compared to patients T2DM-free. Patients who developed T2DM during the follow-up presented higher values of WC, screening, pharmacy frequency, medications and total cost when compared to individuals without T2DM. Being in the highest quartile of PA did not change the costs of health services among patients T2DM-free. Healthcare expenditures were positively correlated to BMI among participants T2DM-free and with T2DM at baseline. Conclusion: Participants with T2DM and participants who developed T2DM during the follow-up showed higher values of BMI, WC, healthcare expenditures and were less active when compared to participants T2DM-free. Healthcare expenditures were positively correlated with BMI among participants with T2DM at baseline and T2DM-free.
Keywords: Body mass index; Body weights and measures; Chronic disease; Diabetes mellitus; Exercise; Public health